The tragedies of Sophocles - Morwood, James (Greece and Rome live., 2014)
This study provides separate discussions of each of Sophocles' seven plays: 'Ajax', 'Women of Trachis', 'Antigone', 'Oedipus the King', 'Electra', 'Philoctetes', and 'Oedipus at Colonus'. It sets these between a chapter that outlines modern approaches to Greek tragedy and a final chapter that spotlights a key moment in the reception of each work. Focusing on the tragedies' dramatic power and the challenges with which they confront an audience, the book refuses to confine them within a supposedly Sophoclean template. They are seven unique works, only alike in the fact that they are all major masterpieces.